A STUDY ON ENGLISH READING HABITS OF STUDENTS OF ENGLISH STUDY PROGRAM OF RIAU UNIVERSITY - Al Nazhari, Hafiz; Delfi, Syofia; ', Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this study is to find out the habits of English reading among the students of English Study Program of Riau University. The method used in this research is quantitative research and the design is survey study. A questionnaire was used as the instrument of this research. The questionnaire involved seven indicators of reading habits: attitudes toward reading, reading frequency, reading materials read, time spend on academic reading, time spend on non-academic reading, motivation in the family environment, and motivation out of the family environment. SPSS Statistics 17.0 program was used to analyse the data. The data analysis displayed only a few number of students who have a habit toward English reading. The finding also proved that the frequency of students in reading English materials was less than 25%. However, the data of attitudes toward reading reveals that most of students (80.2%) aware that reading in English was important for their future. Conducting research to gain a broad overview of the reading habits of EFL learners, the researcher made suggestions to promote English reading habits among university students, especially the students of English Study Program.Keywords: Reading, Reading Habits, Survey Study